Influence of Maternal Factors in Neonatologists' Counseling for Periviable Pregnancies - Kunkel, Melissa D.; Downs, Stephen M.; Tucker Edmonds, Brownsyne (American Journal of Perinatology, 2017)
Background Neonatologists have varying counseling practices for women with threatened periviable pregnancies. Previous research has suggested this variability may be influenced by social and economic factors of the mother.Objective The objective of this study was to determine the relative influence of maternal factors in counseling recommendations for periviable pregnancies.Methods A national cohort of neonatologists was sent a web-based survey. Five maternal characteristics were varied across eight vignettes: age, education, race, parity, and pregnancy “intendedness.” Following each vignette, participants reported their likelihood to recommend full resuscitation versus comfort care. Conjoint analysis was used to assess the relative influence of each factor on respondents' recommendations.Results Responses from 328 neonatologists were included. Of the five tested maternal characteristics, parity and intendedness had the highest importance scores (40.2 and 35.0), followed by race, education, and age. If parents requested resuscitation, respondents were highly likely to comply with preferences, with little variation across vignettes.Conclusion Fetal-specific factors such as gestational age and estimated weight are known to influence counseling and decision making for extremely preterm infants. Our results suggest that maternal factors may also influence counseling practices, although physicians are likely to comply with parental preferences regardless of maternal factors. Future research should identify how maternal characteristics impact actual counseling practices.
Keywords: infant; extremely premature; resuscitation; decision making; parity; race; education status; maternal factors; family characteristics; counseling